Innovation Packages and Scaling Readiness (IPSR) - Rudiger, Udo; Dhehibi, Boubaker; Frija, Aymen; Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2023)
Presentation on Innovation Packages and Scaling Readiness (IPSR) – Delivered on November 9th. This presentation was part of a national face-to-face training session on "CGIAR’s Innovation Packages and Scaling Readiness" for key stakeholders in Tunisia's food system. The event took place on November 9-10, 2023, in Hammamet, Tunisia.